Proceedings Fourth International Conference on MultiAgent Systems
DOI: 10.1109/icmas.2000.858447
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial auction for collaborative planning

Abstract: When rational, utility-maximizing agents encounter an opportunity to collaborate on a group activity, they must determine whether to commit to that activity. We refer to this problem as the initial-commitment decision problem (ICDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
1

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 7 publications
0
78
0
1
Order By: Relevance
“…For example, Tidhar et al [40] and Tambe et al [38] performed role allocation based on matching of capabilities, while Hunsberger and Grosz [18] proposed the use of combinatorial auctions to decide on how roles should be assigned. Modi et al [24] showed how role allocation can be modeled as a distributed constraint optimization problem and applied it to the problem of tracking multiple moving targets using distributed sensors.…”
Section: Role Allocation and Reallocationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tidhar et al [40] and Tambe et al [38] performed role allocation based on matching of capabilities, while Hunsberger and Grosz [18] proposed the use of combinatorial auctions to decide on how roles should be assigned. Modi et al [24] showed how role allocation can be modeled as a distributed constraint optimization problem and applied it to the problem of tracking multiple moving targets using distributed sensors.…”
Section: Role Allocation and Reallocationmentioning
confidence: 99%
“…By enabling the RMTDP to focus its search on incomplete policies, and by providing ready-made decompositions, TOPs assist RMTDPs in quickly searching through the policy space, as illustrated in this section. We focus, in particular, on the problem of role allocation [18,24,40,11], a critical problem in teams. While the TOP provides an incomplete policy, keeping open the role allocation decision for each agent, the RMTDP policy search provides the optimal role-taking action at each of the role allocation decision points.…”
Section: Optimizing Role Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose Computer Producer Agent has received the following two tasks in the same scheduling time window 6 The agent's local scheduler 8 reasons about these two new tasks according to the above information: their earliest start times, deadline, estimated process times and the rewards. It then generates the following agenda which includes the following tasks: Agenda 2.1 [10,26] Purchase Computer A [26,46] Purchase Computer B In this agenda, task Purchase Computer A is scheduled during time range [10,26], and task Purchase Computer B is scheduled during time range [26,46].…”
Section: Detailed Example Of a Multi-linked Negotiation Problemmentioning
confidence: 99%
“…A quantity requirement may be necessary to specify how much resource is needed. 6 The agent will not schedule every time a new task arrives, but will schedule all tasks that fall into the same scheduling time window. 7 The task cannot be started until the contract has been confirmed.…”
Section: Detailed Example Of a Multi-linked Negotiation Problemmentioning
confidence: 99%